Analisis Pengelolaan Retribusi Daerah Sebagai Strategi Peningkatan Pendapatan Asli Daerah (PAD) (Studi Kasus pada Seluruh Organisasi Perangkat Daerah (OPD) Terkait Retribusi di Kabupaten Tulungagung) - Kurniawan, Andy (Jurnal Ilmiah Administrasi Publik, 2019)
Good management of regional levies based on the provisions of the Regional Tax and Retribution Act No. 28 of 2009 is a strategy to optimize income to support regional development. This is important for regional prosperity and becomes a benchmark for regional independence. In-depth analysis of the conditions and developments of the realization of revenue from regional levies can illustrate the problems that occur. The four technical analyzes used were growth analysis, contribution, performance and overlay analysis, which eventually resulted in a description of the object of retribution that had a high leakage rate. Thus a strategy can be formulated that can provide concrete recommendations in order to optimize the receipt of regional retribution as one of the spearheads in increasing PAD inTulungagung District.